Effectiveness of corporate finance valuation methods: Piotroski score in an Ohlson model: the case of Mexico - Durán-Vázquez, Rocío (2014)
This study applied the Piotroski score for 63 selected companies of Mexico, for the period 2005 to 2011. The Piotroski score provides an evaluation on the historical financial performance of a company, with the evaluation of nine financial analysis ratios or criteria. We decided to add this score to the Ohlson Model (which was already tested in previous studies). It was found that the Piotroski score showed statistically significant results in the levels and differences variables. Asymmetric signs were also found in the Piotroski-score variables (levels and lagged), both of them are consistent according to the behavior of the Mexican market. The data were analyzed under a dynamic panel basis, with fixed effects, and the Sargan statistic for this analysis was fulfilled.